Influence of Fraud Triangle on Financial Statement Fraud with Financial Distress as an Intervening Variable: Empirical Study on Financial Sector Companies Listed on the Indonesia Stock Exchange in 2020-2022 - Nurfadilah, Sri; Putra, Wirmie Eka; Ridwan, Muhammad (International Journal of Multidisciplinary Approach Research and Science, 2024)
This study aims to determine the effect of the fraud triangle on financial statement fraud with financial distress as an intervening variable. The population of this study were all financial sector companies totaling 107 and then withdrawing samples using purposive sampling method, there were 42 companies that met the sample criteria. The results showed that pressure affects financial statement fraud, pressure affects financial distress, financial distress affects financial statement fraud, financial distress is able to mediate the relationship between pressure and financial statement fraud, Furthermore, opportunity and rationalization have no effect on financial statement fraud. Opportunity and rationalization have no effect on financial distress. Financial distress is unable to mediate the relationship between opportunity and rationalization with fraudulent financial statements.